Perceptions on Mentoring Concept and Mentoring Practices among Medical Mentors: A Mixed-Methods Study - Cheah, W.L; Helmy, Hazmi; Kiu, Ling Hui; Lee, Sze Ee; Ling, Wei Nii; Wong, Veronica, HS (Universiti Sains Malaysia, 2015)
Introduction: Mentoring medical students is one of the essential responsibilities or missions of a medical school faculty. Objective: This study aimed to determine the perceptions of mentorship and mentoring practices among mentors using a convergent parallel method. Method: Quantitative data was collected by using an adopted validated self-administered questionnaire and analyzed using SPSS version 20. Qualitative data was done using one-to-one interview based on semi structured interview guide and analyzed using thematic analysis. Result: A total of 61 respondents participated in the quantitative survey. Approximately 75% of the respondents had 5 to 10 mentees, with majority rated themselves as satisfactory mentor. More than 60% of them met their mentees at least once every six months. Most respondents were friendly (86.9%) and frank to their mentees (68.9%) and were interested in their mentees’ professional development (95.1%). Phone calling (93.4%) and E-mail (95.1%) were preferred as modes of contact. Mentees were allowed to call their mentors anytime of the day (74.1%). Respondents preferred to counsel their mentees (80.3%) and would refer them for professional help whenever necessary (70.5%). For qualitative data, a total of 5 participants participated with themes emerged: concepts of mentoring, factors contributing to ineffective mentoring and ways to improve mentoring practices. Conclusion: The respondents had positive perceptions regarding their mentorship and practices. A more structured approach with clear mentoring guideline and proper training should be in place.